A PROJECT FEASIBILITY OF CONVERTING LOW-DENSITY POLYETHYLENE AND COAL FLY ASH INTO FUEL - Christine Joy Catindig; Dustin Licos; Jose Marlou Ocaña; Janina Caroline Sayseng; Geleen Tabaldo; Ericka Jade Terrenal (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2023)
Ineptly handled plastic waste has both economic and environmental repercussions. The country's reliance on single-use plastics such as multilayer sachets and pouches has led to the country becoming a